Fragmented self of Gen Z in Instagram: Digital dramaturgy on Bourdieu’s logic of practice - Agustin, Sari Monik; Angeliqa, Fitria (Bricolage : Jurnal Magister Ilmu Komunikasi, 2023)
This research aims to identify the Self formed by Self-Presentation through different social media channels. This presentation of the Self's process is known as Dramaturgy. This study also identifies the Dramaturgy carried out by this study's participants by considering the Doxa, Habitus, Arena, and Capital surrounding the participants. Frameworks of this research are Goffman's Presentation of Self and Dramaturgy; and Bourdieu's Logic of Practice. This research relies on the constructivism paradigm, using a qualitative and in-depth interview to collect data. The founding of this research, Fragmented Self, occurred when participants presented Self on social media. Digital Dramaturgy takes place by considering the participant's Doxa, Habitus, Field, and Capital. The results convey how participants arrange the most likely symbolic Capital by showing their attitude to their impression management. In other fields, participants prefer showing their social Capital through friendship photos or community popularity as the front stage. Others keep their Capital and only stalk friends' social media accounts to be duplicated in other fields. To sum up, the presentation of the Self is fragmented, considering doxa, habitus, arena, and Capital to manage impressions needed in digital Dramaturgy—this Self, namely Fragmented-Self. Keywords: Digital Dramaturgy, Self, Doxa, Habitus, Capital